2004
DOI: 10.1038/sj.bjc.6601551
|View full text |Cite
|
Sign up to set email alerts
|

The CHEK2*1100delC mutation has no major contribution in oesophageal carcinogenesis

Abstract: In response to DNA damage, the cell cycle checkpoint kinase 2 (CHEK2) may phosphorylate p53, Cdc25A and Cdc25C, and regulate BRCA1 function, leading to cell cycle arrest and DNA repair. The truncating germline mutation CHEK2*1100delC abrogates kinase activity and confers low-penetrance susceptibility to breast cancer. We found CHEK2*1100delC in 0.5% of 190 oesophageal squamous cell carcinomas and in 1.5% of 196 oesophageal adenocarcinomas. In addition, we observed the mutation in 3.0% of 99 Barrett's metaplasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Our findings support those of recent case-control studies that have also found no significant association between the CHEK2 1100delC mutation and non -breast cancers (8,(30)(31)(32)(33). There was some evidence for an increase in the risk of cancer before the age of 50 years, although the only cancer sites for which this was statistically significant were lung and colorectal cancer.…”
Section: Discussionsupporting
confidence: 80%
“…Our findings support those of recent case-control studies that have also found no significant association between the CHEK2 1100delC mutation and non -breast cancers (8,(30)(31)(32)(33). There was some evidence for an increase in the risk of cancer before the age of 50 years, although the only cancer sites for which this was statistically significant were lung and colorectal cancer.…”
Section: Discussionsupporting
confidence: 80%
“…In humans, it is located in 22q12.1, and encodes a cell cycle checkpoint kinase that is implicated in DNA damage responses (9,19) . Following the occurrence of double-stranded DNA breaks, CHEK2 is activated through phosphorylation by ATM.…”
Section: Introductionmentioning
confidence: 99%
“…In an esophageal cancer study, Koppert et al found 1.5% of 551 cases and 1.4% of 644 controls carry the CHEK2 ∗ 1100delC mutation [ 63 ]. Similarly, there is no patient with CHEK2 ∗ 1100delC mutation among 91 German head and neck cancer patients [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there is no patient with CHEK2 ∗ 1100delC mutation among 91 German head and neck cancer patients [ 64 ]. Therefore, the authors concluded that the CHEK2 ∗ 1100delC mutation has no major contribution in carcinogenesis in the esophagus [ 63 ] and head and neck [ 64 ].…”
Section: Discussionmentioning
confidence: 99%